Increased Expression of hsa_circ_0002111 and Its Clinical Significance in Papillary Thyroid Cancer - Du, Gongbo; Ma, Runsheng; Li, Hongqiang; He, Jiao; Feng, Kaixiang; Niu, Dongpeng; Yin, Detao (Frontiers in Oncology, 2021)
Circular RNA (circRNA) is a newly discovered non-coding RNA. Recent reports suggest that circRNAs are key regulators of tumourigenesis because of their special structure. In order to investigate the role of hsa_circ_0002111 in papillary thyroid cancer (PTC), we use quantitative real-time polymerase chain reaction (qRT-PCR) to determine the expression pattern of hsa_circ_0002111 in 82 paired PTC and adjacent non-cancerous thyroid tissues. Cell counting kit-8, colony formation, and transwell assays were conducted to assess the effect of hsa_circ_0002111 on PTC cell proliferation, migration, and invasion. We found that the expression of hsa_circ_0002111 was significantly up-regulated in PTC tissues compared with adjacent non-cancerous tissues (P < 0.0001). Expression of hsa_circ_0002111 was also associated with advanced TNM stage and lymph-node metastasis of patients with PTC. The area under the receiver operating characteristic curve was 0.833. Further, cell function assays showed that hsa_circ_0002111 inhibition significantly suppressed the proliferation and invasion abilities of PTC cells in vitro. In conclusions, the study findings show that the over-expression of hsa_circ_0002111 promotes PTC, and thus hsa_circ_0002111 may be a potential diagnostic biomarker and therapeutic target for PTC.